Constraints on an exosphere at Ceres from Hubble Space Telescope observations. Issue 6 (30th March 2016) - Roth, Lorenz; Ivchenko, Nickolay; Retherford, Kurt D.; Cunningham, Nathaniel J.; Feldman, Paul D.; Saur, Joachim; Spencer, John R.; Strobel, Darrell F.
Abstract: We report far ultraviolet observations of Ceres obtained with the Cosmic Origin Spectrograph (COS) of the Hubble Space Telescope in the search for atomic emissions from an exosphere. The derived brightnesses at the oxygen lines at 1304 Å and 1356 Å are consistent with zero signals within the 1 σ propagated statistical uncertainties. The OI 1304 Å brightness of 0.12 ± 0.20 Rayleighs can be explained by solar resonant scattering from an atomic oxygen column density of (8.2 ± 13.4) × 10 10  cm −2 . Assuming that O is produced by photodissociation of H2 O, we derive an upper limit for H2 O abundance and compare it to previous observations. Our upper limit is well above the expected O brightness for a tenuous sublimated H2 O exosphere, but it suggests that H2 O production with a rate higher than 4 × 10 26  molecules s −1 was not present at the time of the COS observation. Additionally, we derive an extremely low geometric albedo of ∼1% in the 1300 Å to 1400 Å range. Key Points: New unprecedented far ultraviolet observations at Ceres with the Hubble Space Telescope Upper limits for oxygen emission are derived and related to upper limits for oxygen abundance The found upper limit for O suggests that H2 O production is not higher than during previous observations